PERLINDUNGAN KONSUMEN TERHADAP TRANSAKSI JUAL BELI KOSMETIK BERMEREKPALSU MELALUI E-COMMERCE - NIM. A1011211067, TUTI WARNI (Jurnal Fatwa Hukum, 2025)
AbstractThe development of digital technology has driven an increase in online buying and selling transactions, including in the cosmetics industry. However, the rampant circulation of counterfeit branded cosmetics through e-commerce has raised various legal issues, particularly concerning consumer protection. This research aims to analyze the legal regulations regarding the buying and selling of counterfeit branded cosmetics through e-commerce, the effectiveness of the enforcement of applicable regulations, and the role of the Food and Drug Supervisory Agency (BPOM) in addressing the circulation of illegal cosmetics.This research uses an empirical juridical method, which involves examining the applicable laws and analyzing the implementation of regulations in practice. Primary data were obtained through structured interviews and questionnaires, while secondary data were obtained through literature studies. Data analysis was conducted qualitatively to obtain a comprehensive understanding of consumer protection in transactions involving counterfeit cosmetics through e-commerce.The research results show that the legal regulations related to the sale and purchase of counterfeit branded cosmetics in e-commerce are based on several key regulations, namely: Law Number 8 of 1999 concerning Consumer Protection (Article 4 and Article 8), Law Number 11 of 2008 concerning Electronic Information and Transactions (Article 9), Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems, and BPOM Regulation Number 12 of 2023 concerning the Supervision of Drugs and Food Circulated Online. These regulations provide a legal basis for consumer protection and the responsibility of e-commerce platforms in ensuring product authenticity. However, despite the regulations being established, there are still obstacles in their implementation, such as weak supervision, difficulty in identifying illegal business operators, and minimal strict sanctions for e-commerce platforms trading counterfeit products. BPOM has a strategic role in monitoring and taking action against the circulation of counterfeit cosmetics through e-commerce, including cyber patrols, inspections of marketplaces, and coordination with digital platforms to remove products that do not have distribution permits. However, the limited authority of BPOM in directly regulating e-commerce activities and the limited number of resources become obstacles in optimizing supervision. In addition to the role of the government and e-commerce platforms, consumers also have a responsibility to protect themselves. Based on Article 5 of the Consumer Protection Law, consumers are required to be cautious in conducting transactions, ensure the legality of products by verifying BPOM distribution permits, and increase awareness of the risks of purchasing counterfeit cosmetics online. Therefore, consumer protection efforts must be carried out collaboratively through increased supervision by the government and BPOM, imposing strict sanctions on e-commerce platforms that violate regulations, and educating consumers to raise awareness of the risks of illegal products.Keywords: Consumer Protection, Buying and Selling Transactions, Fake Branded Cosmetics,E-Commerce  AbstrakPerkembangan teknologi digital telah mendorong peningkatan transaksi jual beli secara daring, termasuk dalam industri kosmetik. Namun, maraknya peredaran kosmetik bermerek palsu melalui e-commerce menimbulkan berbagai permasalahan hukum, terutama terkait dengan perlindungan konsumen. Penelitian ini bertujuan untuk menganalisis pengaturan hukum terhadap transaksi jual beli kosmetik bermerek palsu melalui e-commerce, efektivitas penegakan regulasi yang berlaku, serta peran Badan Pengawas Obat dan Makanan (BPOM) dalam mengatasi peredaran kosmetik ilegal.Penelitian ini menggunakan metode yuridis empiris, yaitu dengan menelaah peraturan Perundang-Undangan yang berlaku serta menganalisis implementasi regulasi dalam praktik. Data primer diperoleh melalui wawancara terstruktur dan kuesioner, sedangkan data sekunder diperoleh melalui studi kepustakaan. Analisis data dilakukan secara kualitatif guna memperoleh pemahaman yang komprehensif terkait perlindungan konsumen dalam transaksi kosmetik palsu melalui e.-commerce.Hasil penelitian menunjukkan bahwa pengaturan hukum terkait transaksi jual beli kosmetik bermerek palsu di e-commerce didasarkan pada beberapa regulasi utama, yaitu: Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen (Pasal 4 dan Pasal 8), Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (Pasal 9), Peraturan Pemerintah Nomor 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik, serta Peraturan BPOM Nomor 12 Tahun 2023 tentang Pengawasan Obat dan Makanan yang Beredar Secara Online. Regulasi tersebut memberikan dasar hukum bagi perlindungan konsumen dan tanggung jawab platform e-commerce dalam memastikan keaslian produk. Namun, meskipun regulasi telah ditetapkan, masih terdapat kendala dalam implementasinya, seperti lemahnya pengawasan, sulitnya identifikasi pelaku usaha ilegal, serta minimnya sanksi tegas bagi e-commerce yang memperdagangkan produk palsu. BPOM memiliki peran strategis dalam pengawasan dan penindakan terhadap peredaran kosmetik palsu melalui e-commerce, termasuk melalui patroli siber, inspeksi terhadap marketplace, serta koordinasi dengan platform digital untuk menghapus produk yang tidak memiliki izin edar. Namun, keterbatasan kewenangan BPOM dalam mengatur langsung aktivitas e-commerce serta jumlah sumber daya yang terbatas menjadi hambatan dalam optimalisasi pengawasan. Selain peran pemerintah dan platform e-commerce, konsumen juga memiliki tanggung jawab dalam melindungi dirinya sendiri. Berdasarkan Pasal 5 Undang-Undang Perlindungan Konsumen, konsumen diwajibkan untuk berhati-hati dalam melakukan transaksi, memastikan legalitas produk dengan memverifikasi izin edar BPOM, serta meningkatkan kesadaran terhadap risiko pembelian kosmetik palsu secara daring. Oleh karena itu, upaya perlindungan konsumen harus dilakukan secara kolaboratif melalui   peningkatan pengawasan oleh pemerintah dan BPOM, pemberian sanksi tegas terhadap e-commerce yang melanggar regulasi, serta edukasi konsumen guna meningkatkan kesadaran akan risiko produk ilegal.Kata Kunci: Perlindungan Konsumen, Transaksi Jual Beli, Kosmetik Bermerek Palsu, E-Commerce